Glycerol monolaurate (GML), a medium-chain fatty acid derivative, ameliorate growth performance, immune function, disease resistance and intestinal microbiota in juvenile hybrid grouper (Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂). Issue 128 (September 2022) - Li, Xuehe; Ray, Gyan Watson; Kou, Shiyu; Liang, Mingning; Yang, Qihui; Tan, Beiping; Chi, Shuyan
Abstract: In order to evaluate the effects of glycerol monolaurate (GML) on the growth performance, immunology function, disease resistance and intestinal microbiota for hybrid groupers. Seven levels of GML (0, 600, 1200, 1800, 2400, 3000 and 3600 mg/kg) were added to diets and were noted as the G1 (control group), G2, G3, G4, G5, G6 and G7, respectively. Each experimental diet was fed to triplicate groups of 30 juvenile groupers for 8 weeks. The FBW, WGR and SGR were significantly higher and FCR was significantly lower in the G4 group compared to the G1 group ( P < 0.05). Serum immune enzyme activities (ACP, AKP and LZM) rose and then fell and had the highest values in the G4 group ( P < 0.05). The expression of TNF-α and IL6 in head kidney was significantly inhibited ( P < 0.05), while the expression of TLR22 was increased ( P < 0.05). After the Vibrio parahaemolyticus challenge test, ACP and AKP activities were increased in the G4 and G5 groups, while mortality was lower than in the G1 group ( P < 0.05). GML significantly modulated the abundance of intestinal microbiota, with the G4 and G5 groups increasing the relative abundance of the Firmicutes and Bacillus, respectively ( P < 0.05). The alpha diversity of the G5 group (Sob, Chao1 and ACE) was significantly higher than that of the G1 group ( P < 0.05). In summary, the optimal level of GML was 1700 mg/kg according to the regression equation model fitted by the WGR index. Highlights: GML can improve the immune function of grouper without side effects or residues. Dietary GML can significantly improved the growth performance, enhanced immunity and promote intestinal health of grouper. Infection rates of Vibrio parahaemolyticus were reduced and immune enzyme activity was enhanced in the group added with GML. In the present experiment, the optimal dietary GML requirement is 1700 mg/kg for juvenile grouper.